The new world of poly-(ADP)-ribose polymerase inhibitors (PARPi) used in the treatment of gynecological cancers. Issue 10 (14th September 2020) - Chelariu-Raicu, Anca; Zibetti Dal Molin, Graziela; Coleman, Robert L
Abstract : The clinical development of poly-(ADP)-ribose polymerase inhibitors (PARPi) began with the treatment of ovarian cancer patients harboring BRCA1/2 mutations and continues to be expanded to other gynecological cancers. Furthermore, The Cancer Genome Atlas (TCGA) analysis of endometrial and cervical cancers offered rationale that PARPi may be an option for treatment based on the molecular profiles of these cancer types. This review summarizes the current indications of PARPi, such as its role in the treatment and maintenance of recurrent ovarian cancer and for first-line maintenance therapy in advanced ovarian cancer. We also outline new concepts for PARPi therapy in other gynecological cancers such as endometrial and cervical cancers based on recent clinical data. Finally, we present potential future directions to continue exploring the world of PARPi resistance and combining PARPi with other therapies.